Voice and agency: workers with a disability and trade unionism. (2nd January 2019) - Brigden, Cathy
ABSTRACT: Workers with a disability have long recognised the benefits of organising collectively, with union representation and protection regarded as critical in enabling voice and agency in pursuit of workplace rights. Understanding the nature of disability at work requires recognising the differences between workers who come to the workplace with a pre-existing disability or illness and those whose disability or illness is work-related, through exposure to hazardous substances and practices. To explore organising strategies adopted by these workers, the historical use of separate organising by workers with a vision-impairment is viewed through the formation and activism of Blind Workers Unions in Australia. The importance of generating voice and agency is examined by reference to media depictions of blind workers' bodies. Informed by the 'bodily' turn in labour history, together with the new disability history, identifying how voice and agency were expressed through both the blind workers' unions and the broader labour movement reinforces how separate organising can underpin solidarity.